2020
DOI: 10.3390/inventions6010002
|View full text |Cite
|
Sign up to set email alerts
|

A New Project for a Much More Diverse Moroccan Strategic Version: The Generalization of Solar Water Heater

Abstract: This paper presents a strategical project for the new version of the Moroccan energy policy. It highlights the technology of solar water heaters (SWH), studying energy, economic and environmental gains of SWH generalization to satisfy the total resident need proposing a new strategic version diversified in terms of adopted technologies (more than green electricity). A detailed analysis of thermal performances and economic profitability of direct thermosyphon solar water heaters (TSWH) for residential requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Figure 1 above presents essential data concerning the butane industry in Morocco [18,19]. The majority of these statistics are sourced from public information provided by reputable institutions such as the Moroccan Ministry of Economy and Finance.…”
Section: Statistical Overview Of Butanementioning
confidence: 99%
“…Figure 1 above presents essential data concerning the butane industry in Morocco [18,19]. The majority of these statistics are sourced from public information provided by reputable institutions such as the Moroccan Ministry of Economy and Finance.…”
Section: Statistical Overview Of Butanementioning
confidence: 99%
“…In total, 15 papers were submitted to this Special Issue, and out of them, 10 were selected for publication. The accepted articles in this Special Issue cover a variety of topics, ranging from energy forecasting and the techno-economic analysis of renewable-based energy systems [1][2][3] to their hybridization [4,5], control [6,7] and integration [8][9][10].…”
Section: Emerging Technologies For Modern Energy Systemsmentioning
confidence: 99%
“…In [8], the generalization of solar water heater systems in Morocco and their potential energy-saving, economic and environmental benefits were presented. In particular, the authors analyzed the thermal performances and economic benefits of direct thermosyphon solar water heaters (TSWHs) for residential requirements in Morocco.…”
Section: Emerging Technologies For Modern Energy Systemsmentioning
confidence: 99%
“…Many studies have been reported on the analysis, design and estimate of the Moroccan regions potential to implant different solar technologies for various applications [6][7][8][9][10]. A. Allouhi et al [11] estimated the technical feasibility of solar water heaters (SWH) under Moroccan conditions in six different regions for two technologies: flat plate and evacuated tube collector.…”
Section: Introductionmentioning
confidence: 99%